Pan-phylum In Silico Analyses of Nematode Endocannabinoid Signalling Systems Highlight Novel Opportunities for Parasite Drug Target Discovery - Crooks, Bethany A.; Mckenzie, Darrin; Cadd, Luke C.; McCoy, Ciaran J.; McVeigh, Paul; Marks, Nikki J.; Maule, Aaron G.; Mousley, Angela; Atkinson, Louise E. (Frontiers in Endocrinology, 2022)
The endocannabinoid signalling (ECS) system is a complex lipid signalling pathway that modulates diverse physiological processes in both vertebrate and invertebrate systems. In nematodes, knowledge of endocannabinoid (EC) biology is derived primarily from the free-living model species Caenorhabditis elegans, where ECS has been linked to key aspects of nematode biology. The conservation and complexity of nematode ECS beyond C. elegans is largely uncharacterised, undermining the understanding of ECS biology in nematodes including species with key importance to human, veterinary and plant health. In this study we exploited publicly available omics datasets, in silico bioinformatics and phylogenetic analyses to examine the presence, conservation and life-stage expression profiles of EC-effectors across phylum Nematoda. Our data demonstrate that: (i) ECS is broadly conserved across phylum Nematoda, including in therapeutically and agriculturally relevant species; (ii) EC-effectors appear to display clade and lifestyle-specific conservation patterns; (iii) filarial species possess a reduced EC-effector complement; (iv) there are key differences between nematode and vertebrate EC-effectors; (v) life stage-, tissue- and sex-specific EC-effector expression profiles suggest a role for ECS in therapeutically relevant parasitic nematodes. These data also highlight putative novel targets for anthelmintic therapies. To our knowledge, this study represents the most comprehensive characterisation of ECS pathways in phylum Nematoda and inform our understanding of nematode ECS complexity. Fundamental knowledge of nematode ECS systems will seed follow-on functional studies in key nematode parasites to underpin novel drug target discovery efforts.